Optimisation studies on removal of fluoride by micellar enhanced ultrafiltration. (2023) - Mukunda Vani, M.; Shruthi Keerthi, D.; Sridhar, Sundergopal
Abstract: Removal of fluorine from water is one of the key problems in supply of pure drinking water. Permissible limit of fluoride in drinking water was determined to 1.5 ppm by world health organization. There are different techniques for fluoride removal like ion-exchange, precipitation, adsorption, and membrane techniques but this can be more effective through one membrane technique which is Micellar Enhanced Ultrafiltration (MEUF). In this method surfactants create micelles, which are retained by ultrafiltration membranes. Application of MEUF process for removal of fluoride was studied using polyethersulfone (PES) based ultrafiltration membranes and cationic surfactant (cetylpyridinium chloride-CPC) in batch process. The PES membranes prepared by phase inversion method was ultra-porous in nature with a molecular weight cut-off (MWCO) of 50 kDa. A 20-run factorial design was performed using central composite design (CCD) with Response surface methodology (RSM) to optimize fluoride removal using micellar enhanced ultrafiltration. The effect of different variables like surfactant concentration, pressure drop and time on fluoride removal was investigated in this study. The statistical analysis indicated that among the parameters tested, surfactant concentration, time, interaction between surfactant concentration and pressure drop and pressure drop, and time had a significant effect on reduction of fluoride concentration. A correlation coefficient of R 2 = 0.9672 indicated the model was adequate to predict the reduction of fluoride concentration with optimum conditions at surfactant concentration (3 CMC (critical micelle concentration)), pressure drop (7 kg/cm 2 ) and 30 mins of time with 0.79 ppm of fluoride concentration.